2005
DOI: 10.1007/s11104-004-0231-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus enrichment and balance in forests colonized by cormorants: Implications of the influence of soil adsorption

Abstract: Although much concern has been directed at nitrogen (N) cycling in terrestrial ecosystems with bird colonies, little has been clarified on the processes of phosphorus (P) cycling itself, and few comparisons between P and N cycling in bird colonies have been made. On the Isaki Headland and Chikubu Island, which are located on or near the shore of Lake Biwa, Central Japan, a dramatic increase in the population of cormorants has occurred since the 1980s. There has been a concomitant increase in the transport of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 35 publications
5
66
1
Order By: Relevance
“…Over time cormorants, especially in dense colonies, increase N and P content in soil layers to extreme extents (Ligęza & Smal, 2003;Hobara et al, 2005;Kolb et al, 2012;Rush et al, 2013;Litaor et al, 2014;Klimaszyk et al, 2015b). However, even a small cormorant flock can induce a short-term rise in their concentrations, usually restricted to period the birds are present (Klimaszyk et al, 2015b).…”
Section: Soil Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Over time cormorants, especially in dense colonies, increase N and P content in soil layers to extreme extents (Ligęza & Smal, 2003;Hobara et al, 2005;Kolb et al, 2012;Rush et al, 2013;Litaor et al, 2014;Klimaszyk et al, 2015b). However, even a small cormorant flock can induce a short-term rise in their concentrations, usually restricted to period the birds are present (Klimaszyk et al, 2015b).…”
Section: Soil Chemistrymentioning
confidence: 99%
“…In this form, N accumulates mainly in the surface soil layer (Ligęza & Smal, 2003) and may undergo volatilization (Mizutani & Wanda, 1988;Mulder & Keall, 2001;Ligęza & Smal, 2003;Hobara et al, 2005). The intensity of this process depends, however, on variables such as pH, soil moisture and temperature (Loder et al, 1996).…”
Section: Soil Chemistrymentioning
confidence: 99%
“…It is highly plausible that the large quantities of nutrients observed in soils beneath a developing roosting colony are brought about by the greater density of great cormorants in comparison to perennial nesting colonies. Compared to other colonies (Ligęza et al 2001;Hobara et al 2001Hobara et al , 2005, the deeper soil layers under the roosting colony at Lake Góreckie contain smaller quantities of N and P. The impact of the great cormorants on soil chemistry is only traceable to the depth of 20 cm.…”
Section: Discussionmentioning
confidence: 79%
“…Some literature data suggested that the transfer of N and P from soils under great cormorant colonies into groundwater is minimal. In forest pressured by cormorants, volatilization of ammonia into the atmosphere is predominant whereas P is effectively accumulated in soils (Mulder and Keall 2001;Hobara et al 2005;Osono et al 2006). We found that surface runoff promotes the elution of N, P and other chemicals from soils beneath the colony.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation